A Dirichlet problem with asymptotically linear and changing sign nonlinearity - Lucia, Marcello; Magrone, Paola; Zhou, Huan-Song (Revista Matemática Complutense, 2003)
This paper deals with the problem of finding positive solutions to the equation ¡¢u = g(x; u) on a bounded domain ; with Dirichlet boundary conditions. The function g can change sign and has asymptotically linear behaviour. The solutions are found using the Mountain Pass Theorem.